Actions specialist forensic examination at the place of an act of terrorism using explosives and explosives (International relations and international law Journal, 2016)
In article the place of acts of terrorism with use of explosive devices and explosives is considered features action of the specialist criminalist at survey. In due time and qualitatively performed inspection of the scene gives the chance of obtaining the important actual data relating to all circumstances entering a proof subject. Timely detection and research of material and ideal traces of terrorist explosion allows to receive information on the used explosive device, its separate characteristics, a way of detonation, to define a type of the used explosive and its trotyl equivalent, location of the explosive device at the time of explosion, existence at the criminal of professional skills.
Keywords: the specialist criminalist; an act of terrorism; terrorist explosion; survey; detection and fixing